2006
DOI: 10.1002/hep.21253
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir for patients with lamivudine-resistant hepatitis B virus (HBV) infection and high HBV DNA level during adefovir therapy

Abstract: Incomplete virological response to adefovir dipivoxil (ADV) has been observed in patients with lamivudine-resistant hepatitis B virus (HBV) infection and may be associated with developing resistance and disease progression. We therefore investigated whether the efficacy of viral suppression could be improved by replacing ADV with tenofovir disoproxil fumarate (TDF). Twenty patients with chronic HBV infection (18 HBeAg؉), viral breakthrough during lamivudine therapy, and persistent viral replication (>10 4 copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
182
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(199 citation statements)
references
References 35 publications
9
182
0
8
Order By: Relevance
“…TDF + LAM group was superior to other groups (Table 3). Van Bommel et al [13] not only found the higher potency of TDF over ADV in treatment naive patients with hepatitis B, but also among patients with LAM resistance who showed incomplete response to ADV in patients [20]. Furthermore, Del Poggio et al [21] found that low-dose TDF (75 mg) was more potent than adefovir (10 mg) in chronic HBeAg-negative hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…TDF + LAM group was superior to other groups (Table 3). Van Bommel et al [13] not only found the higher potency of TDF over ADV in treatment naive patients with hepatitis B, but also among patients with LAM resistance who showed incomplete response to ADV in patients [20]. Furthermore, Del Poggio et al [21] found that low-dose TDF (75 mg) was more potent than adefovir (10 mg) in chronic HBeAg-negative hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…With tenofovir treatment, the serum HBV DNA-negative conversion rate for patients without adefovir-resistance was 100%, but the rate was down to 52% for patients with adefovir-resistance [89] . An important feature of tenofovir is that tenofovir alone or with emtricitabine exerts an anti-viral effect to lamivudine, adefovir or entecavir resistance mutants [85,86,93,95,96] . For example, an article reported that for patients who achieved an insufficient effect by lamivudine, adefovir or the combination of these two drugs, tenofovir resulted in a serum HBV DNA-negative conversion rate of 79%, HBeAg-negative conversion rate of 24% and HBsAg-negative conversion rate of 3% of all patients (the median time from administration to HBsAg-negative conversion was 23 mo) [86] .…”
Section: Tenofovir Disoproxil Fumarate (Tenofovir)mentioning
confidence: 99%
“…Increased dosage to 20 mg daily with careful monitoring of renal function achieved better efficacy and can be considered in patients with elevated ALT levels, severe, or rapidly progressive liver disease [80].…”
Section: Management Strategy For Lamivudine Resistancementioning
confidence: 99%
“…Before the availability of adefovir in some region, tenofovir has been used successfully for lamivudine resistance [132]. Subsequent switch back to adefovir resulted in viral relapse in 60% of patients.…”
Section: Tenofovirmentioning
confidence: 99%